2021
DOI: 10.3390/tropicalmed6020099
|View full text |Cite
|
Sign up to set email alerts
|

Natural Infection and Vertical Transmission of Zika Virus in Sylvatic Mosquitoes Aedes albopictus and Haemagogus leucocelaenus from Rio de Janeiro, Brazil

Abstract: Zika virus (ZIKV) was recently introduced into the Western Hemisphere, where it is suspected to be transmitted mainly by Aedes aegypti in urban environments. ZIKV represents a public health problem as it has been implicated in congenital microcephaly in South America since 2015. Reports of ZIKV transmission in forested areas of Africa raises the possibility of its dispersal to non-human-modified environments in South America, where it is now endemic. The current study aimed to detect arboviruses in mosquitoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
1
21
0
6
Order By: Relevance
“…This lineage displayed higher transmissibility in Aedes aegypti than ZIKV AS , and it was also verified to mosquitoes from South American (Aubry et al, 2021). Alencar et al (2021) found Ae. albopictus naturally infected with ZIKV AF in the Southeast of Brazil, recovered from the Atlantic Forest.…”
Section: Zika Virus: Epidemiological Profile and A Threat Of New Outbreaksmentioning
confidence: 52%
See 2 more Smart Citations
“…This lineage displayed higher transmissibility in Aedes aegypti than ZIKV AS , and it was also verified to mosquitoes from South American (Aubry et al, 2021). Alencar et al (2021) found Ae. albopictus naturally infected with ZIKV AF in the Southeast of Brazil, recovered from the Atlantic Forest.…”
Section: Zika Virus: Epidemiological Profile and A Threat Of New Outbreaksmentioning
confidence: 52%
“…Eventually, these vectors may be carrying ZIKV, regardless of the lineages and supporting a possible establishment of a sylvatic cycle, critical for the arbovirus maintenance (Lowe et al, 2018;Giovanetti et al, 2020). Recently, ZIKV AF circulation in mosquitoes and NHPs in sylvatic areas in Brazil was evidenced (Figure 1) (de Almeida et al, 2019-Preprint publication; Alencar et al, 2021). This lineage displayed higher transmissibility in Aedes aegypti than ZIKV AS , and it was also verified to mosquitoes from South American (Aubry et al, 2021).…”
Section: Zika Virus: Epidemiological Profile and A Threat Of New Outbreaksmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the Zika virus was identified in Ae. albopictus in six studies carried out in Brazil (n = 4) and Mexico (n = 2) [14,47,53,54,57,59].…”
Section: Natural Infections Of Ae Albopictus With Arbovirusesmentioning
confidence: 99%
“…Additionally, yellow fever virus was isolated in Ae. albopictus females in Rio de Janeiro State, which could imply that it could be acting as an additional jungle or rural vector causing a possible transmission bridge to the urban area [47].…”
Section: Introductionmentioning
confidence: 99%